FEATURES OF FORMING OF URANIUM MINERALIZATION IN SODIUM METASOMATITES OF NOVA-KONSTYANTYNIVKA URANIUM DEPOSITES - Emets, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper provides results of mineralogical investigations of the Novokostantynivka U deposit. Successive formation (replacements) of mineral paragenesises reveals three different types of metasomatic alterations (from the earliest to the latest): Nametasomatism, Ca-metasomatism and K-metasomatism. U-ores in the deposit are composed by uraninite, brannerite and unidentified mineral with chemical composition similar to davidite. A major stage of U accumulation was manifested by Ca- and K-metasomatism, along with dissolution of albitites. A model of U-mineral crystallization in the deposit is demonstrated from a range of mineralogical and geochemical regularities. This model shows that U-ores were formed during reduction of hexavalent uranium to quadrivalent uranium because of presence of reduction barrier which was strongly controlled by divalent iron minerals in albitites: mostly by magnetite but also by ilmenite, aegirine and amphiboles: U6+ solution+2Fe2+ mineral→ U4+ mineral+ 2Fe3+ solution/hematite.